2007
DOI: 10.1161/circresaha.107.159053
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ca 2+ -Independent Phospholipase A 2 and Store-Operated Pathway in Urocortin-Induced Vasodilatation of Rat Coronary Artery

Abstract: Abstract-Urocortin has been shown to produce vasodilatation in several arteries, but the precise mechanism of its action is still poorly understood. Here we demonstrate the role of store operated Ca 2ϩ entry (SOCE) regulated by Ca 2ϩ -independent phospholipase A 2 (iPLA 2 ) in phenylephrine hydrochloride (PE)-induced vasoconstriction, and we present the first evidence that urocortin induces relaxation by the modulation of SOCE and iPLA 2 in rat coronary artery. Urocortin produces an endothelium independent rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 45 publications
3
49
0
Order By: Relevance
“…A full colour version of this figure is available via http:dx.doi.org/10.1530/ JME-13-0182. rat coronary artery (Smani et al 2007). Consistent with the results of Lawrence et al, Takatani-Nakase & Takahashi (2010) found that Ucn1 could significantly suppress the expression and activity of iPLA2, which results in prevention of the ischemia-induced cell death.…”
Section: Figuresupporting
confidence: 79%
“…A full colour version of this figure is available via http:dx.doi.org/10.1530/ JME-13-0182. rat coronary artery (Smani et al 2007). Consistent with the results of Lawrence et al, Takatani-Nakase & Takahashi (2010) found that Ucn1 could significantly suppress the expression and activity of iPLA2, which results in prevention of the ischemia-induced cell death.…”
Section: Figuresupporting
confidence: 79%
“…In rat mesenteric artery, vasoactive intestinal polypeptide caused relaxation through PKA-stimulated K ATP channels (73). Storeoperated Ca 2ϩ entry was also demonstrated to be involved in coronary artery relaxation mediated by a PKA-dependent mechanism under urocortin treatment (62). Thus, it seems that ion channels, especially BK Ca channels, play an important role in PKA-mediated vascular smooth muscle relaxation by lowering intracellular Ca .…”
Section: Discussionmentioning
confidence: 97%
“…However, other pathways have been reported to be activated by stimulation of CRFRs such as (ERK)-MAP kinase, AKT/protein kinase B and nitric oxide synthase-guanylyl cyclase (Grammatopoulos et al 2000, Cantarella et al 2001, Bayatti et al 2003, Karteris et al 2005. The intracellular signalling pathways activated by UCN in osteoclasts remain unknown, but intracellular Ca 2C signalling has been shown to be crucial for maintaining osteoclastic differentiation (Boyce & Xing 2007) and UCN has been shown to inhibit store-operated Ca 2C entry in vascular smooth muscle cells (Smani et al 2007, Negishi-Koga & Takayanagi 2009). Therefore, channels that regulate Ca 2C entry are potential candidates as a target for UCN in osteoclasts.…”
Section: Discussionmentioning
confidence: 99%
“…In other cell types, UCN has been shown to regulate cellular functions by inhibiting ion channels involved in promoting Ca 2C influx, such as voltage-dependent and -independent Ca 2C -permeable channels (Tao et al 2004, Smani et al 2007. Extracellular Ca…”
Section: Non-selective Cation Channel Blockers Inhibit Actin Ring Formentioning
confidence: 99%
See 1 more Smart Citation